HUBUNGAN PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) DENGAN KUALITAS LAPORAN KEUANGAN - Heryana, Toni; Sartono Rahman, Ano (Program Studi Akuntansi FPEB UPI, 2013)
This study aims to find out (1) the implementation of ERP in seven state-owned enterprises in Bandung, (2) the quality of financial statements in seven state-owned enterprises in Bandung that have implemented ERP, and (3) how the relationship of ERP implementation with the quality of financial statements at seven state- Bandung. The variables tested were Enterprise Resource Planning (ERP) and quality of financial statements. This study uses primary data for both variables in the form of questionnaires to seven State-Owned Enterprises in Bandung.The method used in this research is descriptive method. Population in this research is 20 SOEs in Bandung that have implemented ERP. Sampling technique used is Convenience Sampling so taken 7 SOEs from the population as a sample. The unit of analysis in this study is the financial manager. The hypothesis proposed in this study is